ARTIFACTUAL LOCALIZATION OF FERRITIN IN THE CILIARY EPITHELIUM IN VITRO - Tormey, John Mcd. (The Rockefeller University Press, 1965)

(untitled)
The accumulation of ferritin by the ciliary epithelium of the adult albino rabbit has been studied by electron microscopy. The experiments have been carried out under in vitro conditions, such that any uptake observed should be the result of passive diffusion of the tracerparticles rather than the product of active metabolic processes. The cells were fixed in osmium tetroxide and embedded in Araldite. Ferritin was found localized in three areas: in rows of apparent vesicles, free in the cytoplasmic matrix, and in the basement membrane. Some of the conclusions reached are as follows. The appearance of tracer in rows of vesicles is not in itself an adequate demonstration of pinocytosis. The permeability of the plasma membrane is drastically increased by osmium tetroxide fixation, so that tracer particles are free to diffuse across the membrane and wander through the cytoplasm. These results indicate the serious danger of being misled by artifacts when colloidal particles are used as tracers.